Concomitant versus sequential therapy for the treatment of Helicobacter pylori infection: a Greek randomized prospective study. (1st February 2016) - Apostolopoulos, Periklis; Koumoutsos, Ioannis; Ekmektzoglou, Konstantinos; Dogantzis, Panagiotis; Vlachou, Erasmia; Kalantzis, Chrisostomos; Tsibouris, Panagiotis; Alexandrakis, Georgios
Abstract: Objective : The objective of this study is to compare, in Greece, a region with >20% local resistance to clarithromycin, the efficacy rates of the concomitant versus the sequential H. pylori eradication therapy. Materials and methods : Our prospective randomized study included 364 patients with newly diagnosed H. pylori infection, randomized to receive a 10-day concomitant or 10-day sequential therapy. Treatment outcome was assessed by C 13 -urea breath test at least 4 weeks after therapy. Intention to treat (ITT) and per protocol (PP) analysis of the eradication rates were performed. Secondary end points included patient compliance and safety. Results : The concomitant therapy group achieved statistically significant higher eradication rates when compared with the sequential treatment group, both in the ITT and in the PP analysis (84.6% versus 70.9%, p  = 0.002, and 90.6% versus 78.1%, p  = 0.001, respectively), after adjusting for age, gender, smoking status, and the presence or not of ulcer and/or non-ulcer dyspepsia. Both groups displayed excellent compliance rates (99.5% for the concomitant therapy group and 96.2% for the sequential therapy group, p  = 0.067). Regarding treatment safety, major adverse events that led to the discontinuation of both regimens were few, with no statistical difference between the two groups (7.0% for the concomitant therapy group and 2.9% for the sequential therapy group). Conclusions : Concomitant therapy led to statistically significant higher eradication rates over sequential therapy. Both therapies showed excellent compliance and an acceptable safety profile. The 10-day quadruple concomitant scheme should be the adopted for first-line H. pylori eradication in Greece.